Conker - Morpurgo, Michael; Turley, Gerry (Egmont London, 2002)
The story revolves around a boy named Nick who finds solace in conker (horse chestnut) collecting and battling, a popular game among children. However, his joy is overshadowed by his experiences with a local bully named Stevie Rooster and the emotional turmoil of watching his dog, Patch, suffer as it grows older and sick. While escaping from Stevie one day, Nick finds a conker in the woods that he believes will be unbeatable in the playground games. At the same time, his personal life takes a serious turn when he must face the prospect of letting go of Patch. Through this dual struggle, Nick learns about bravery, compassion, and the value of confronting challenges rather than avoiding them. With the help of his grandmother and his friendships, Nick discovers how to stand up to Stevie, say goodbye to Patch, and face life's difficult moments with courage. Michael Morpurgo$1 (Bs storytelling masterfully explores how children can navigate complex emotions like grief, fear, and self-worth, presenting these themes in a way that is both accessible and meaningful to young readers. The use of the conker serves as a metaphor for resilience and inner strength, which are central to the book's message. It's a touching story about emotional growth and finding strength in the face of adversity.s